Finite Element Analysis of Two Nearby Interfering Strip Footings Embedded in Saturated Cohesive Soils - Mo'men Ayasrah; Mohammed Y. Fattah (Civil Engineering Journal, 2023)
The issue of interaction between nearby footings is of paramount practical significance. The interference effect should be taken into account since the footing may really be separated from or bounded by other footings on one or both sides. In this regard, this paper studies the effect of two nearby interfering strip footings embedded in saturated cohesive soils, which will help to provide a better understanding of the impact of footing depth on the interference effect. A numerical study is carried out using the finite element program (Midas GTS-NX), and the behavior of closely placed strip footings embedded in the saturated cohesive soils is investigated under the influence of different factors such as the spacing between footings, the depth of footings, soil undrained shear strength, and the groundwater table. It was concluded that the soil cohesion and the footing depth ratio have a notable influence on the interference of closely spaced footings. For all cohesion values, it has been observed that the spacing needed for interference to vanish decreases with an increase in the depth of the footing and water table. In addition, as the S/B ratio increases, the ultimate bearing capacity (UBC) of interfering footings decreases until it reaches the same value as an isolated footing at greater spacing. The UBC is approximately 10% higher at S/B = 1 compared to the isolated footing. However, at S/B = 1, the UBC of two footings achieves a value equal to that of an isolated footing and does not change when the S/B ratio increases. With increasing footing depth, there is an increase in UBC. Finally, the highest values of x were obtained in all cases when Cu = 40 kPa. This indicates that the interaction between footings is greater when the soil is softer. Doi: 10.28991/CEJ-2023-09-03-017 Full Text: PDF